PENERAPAN METODE USER CENTERED DESIGN (UCD) PADA PERANCANGAN USER INTERFACE APLIKASI PEMBELAJARAN PEMPROGRAM WEB - Deswara, Muhammad Bayu (Universitas Mahakarya Asia, 2024)
Web programming learning is an in-depth introduction that teaches people how to design, develop, and maintain websites. By learning programming languages, frameworks, and best practices, this course allows students to develop their creativity by creating innovative and responsive technological solutions for the ever-changing digital world. This research explores the application of User Centered Design (UCD) Method in designing the user interface for web programming learning application. This method results in a design that is responsive to user needs and preferences by putting the user first. The application interface can increase learning engagement and make learning more enjoyable by applying UCD principles. The results of this study show that the user-centered method significantly improves the quality and efficiency of web programming learning applications.